Components of the decision to purchase Domestika platform courses through YouTube - Altamirano-Sifuentes, Daniela (2024)
Currently, there is a great demand for online courses on platforms such as Coursera, Domestika, among others. This growth has increased since the Covid-19 pandemic. Therefore, this study analyzes the perceptions of young university students between 20 and 30 years of age from the Faculty of Communications of a private university in Lima, Peru, to understand what the elements of purchase decision in the advertising communication of the Domestika e-learning platform through pre-roll content on YouTube are. The approach of the study is qualitative with a case study design. Sixteen semi-structured interviews were conducted with university students who use the YouTube platform as an educational, entertainment, etc. tool. Accordingly, the purchase decision components were determined: the quality of the teachers, the self-improvement discourse, and the online proposal in pandemic.